The Cognitive Linguistic Analysis of Conceptual Metaphor in Yomiuri Shinbun and Asahi Shinbun on COVID-19 Discourses - Prasetya, Dany Buyung Yudha; Oesman, Andy Moorad (Universitas Negeri Semarang, 2024)
In communicating ideas in a complex discourse, non-literal expressions are often used to convey a message. This qualitative descriptive study used conceptual metaphor theory and metaphorical pattern analysis to analyze and investigate linguistic discourses and find the conceptual metaphor in the two most prominent Japanese media, Yomiuri Shinbun and Asahi Shinbun. Then, analyze how metaphorical expression emerges and what conceptual domain of the source domain is underlying the expression of the source target. This research shows that WAR is the most frequent conceptual metaphor in COVID-19 discourse and the HUMAN and NATURE conceptual domain. While the WAR conceptual domain helps to convey the urgency of how to treat the virus and illness, the HUMAN and NATURE conceptual domain helps to convey the situation and condition of the pandemic. This study found that both newspapers' data emphasize the community, citizens, and national interests, indicating that to understand how Japanese people communicate is to understand that Japanese people are a collective society, and that society and cultural background are embodied in the conceptual domain of human thinking and then appear as a linguistic expression.